Generic features of the primary relaxation in glass-forming materials (Review Article) - Kokshenev, Valery B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We discuss structural relaxation in molecular and polymeric supercooled liquids, metallic alloys and orientational glass crystals. The study stresses especially the relationships between observables raised from underlying constraints imposed on degrees of freedom of vitrification systems. A self-consistent parametrization of the α-timescale on macroscopic level results in the material-and-model independent universal equation, relating three fundamental temperatures, characteristic of the primary relaxation, that is numerically proven in all studied glass formers. During the primary relaxation, the corresponding small and large mesoscopic clusters modify their size and structure in a self-similar way, regardless of underlying microscopic realizations. We show that cluster-shape similarity, instead of cluster-size fictive divergence, gives rise to universal features observed in primary relaxation. In all glass formers with structural disorder, including orientational-glass materials (with the exception of plastic crystals), structural relaxation is shown to be driven by local random fields. Within the dynamic stochastic approach, the universal subdiffusive dynamics corresponds to random walks on small and large fractals.